Professionalization and trust in public sector interpreting. - Skaaden, Hanne (International Journal of Language, Translation and Intercultural Communication, 2016)
This article approaches interpreting in the public sector or “community” from the vantage point of the sociology of professions. The aim is to examine the interpreter function in light of the process of professionalization and concepts such as professional trust and the exercise of discretion. How well does the interpreter function fulfill the criteria of being a profession? What is holding the process of professionalization back? In exploring these issues, I observe the interpreter function through the prism of a model of professionalization outlined by a group of Scandinavian sociologists (Molander & Terum, 2008; Grimen 2008ab; Grimen & Molander, 2008). The model divides professionalization into performative and organizational aspects. What is the professional status of the interpreter in the public sector in terms of these aspects? The empirical data originate from chat discussions where students with different working languages (WL) who are going through a blended course (30 ECTS) on interpreting, discuss issues of professionalization. The analysis shows that the interpreter function fulfills the criteria of the performative aspect, while the organizational aspect is less developed.